2020
DOI: 10.12968/bjon.2020.29.13.770
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve inpatients' sleep quality in intensive care units and acute wards: a literature review

Abstract: Background: Sleep is essential for the physical and psychological restoration of inpatients, and lack of sleep results in sleep deprivation and poor sleep quality, with potentially harmful consequences. Aim: To summarise sleep-promoting interventions in the Intensive care unit (ICU) and acute ward setting. Method and results: Six databases were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
(29 reference statements)
0
9
0
1
Order By: Relevance
“…The effects of different non-pharmacological sleep promotion methods have mostly been studied in ICU settings (Cooke et al, 2020). Aparicio and Panin (2020) found four studies performed in acute ward setting and concluded that only light conditions and the use of sleep medications varied between ICUs and acute wards. A multi-component sleep promotion protocol including the control of the environment, minimisation of care interventions and a sleep hygiene teaching session has proven to be feasible (Gathecha et al, 2016).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The effects of different non-pharmacological sleep promotion methods have mostly been studied in ICU settings (Cooke et al, 2020). Aparicio and Panin (2020) found four studies performed in acute ward setting and concluded that only light conditions and the use of sleep medications varied between ICUs and acute wards. A multi-component sleep promotion protocol including the control of the environment, minimisation of care interventions and a sleep hygiene teaching session has proven to be feasible (Gathecha et al, 2016).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The findings in this study also support the findings of our study. Environmental noise has been found in several studies as the most common factor responsible for sleep interruptions [ 14 , 15 ]. The fact remains that it is difficult to find the ideal amount of sleep for every patient in different medical settings who is suffering from a particular disease and has comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Several areas for improvement identified in this survey involve the physical environment of the NTICU, such as high noise levels, the small waiting room, lack of privacy, and the lack of bathrooms. There is a large body of literature on the negative impact of sleep deprivation in ICUs, with mitigation of environmental factors seen as key to improving sleep 20‐22 . Of note, construction (which included jackhammering on the roof and laying of new cement) inside the unit was ongoing during the daytime hours from February 2017 to November 2017.…”
Section: Discussionmentioning
confidence: 99%
“…There is a large body of literature on the negative impact of sleep deprivation in ICUs, with mitigation of environmental factors seen as key to improving sleep. [20][21][22] Of note, construction (which included jackhammering on the roof and laying of new cement) inside the unit was ongoing during the daytime hours from February 2017 to November 2017. Also, at one point the family waiting room was closed for few weeks.…”
Section: Areas For Improvementmentioning
confidence: 99%